Impact of bias conditions on electrical stress and ionizing radiation effects in Si-based TFETs. (January 2016) - Ding, Lili; Gnani, Elena; Gerardin, Simone; Bagatin, Marta; Driussi, Francesco; Selmi, Luca; Royer, Cyrille Le; Paccagnella, Alessandro
Abstract: The interplay between electrical stress and ionizing radiation effects is experimentally investigated in Si-based Tunnel Field Effect Transistors (TFETs). In particular, the impact of bias conditions on the performance degradation is discussed. We found that the electrical stress effects in TFETs could not be ignored in radiation tests, since they can possibly overwhelm the radiation-induced degradation. Under this circumstance, the worst-case bias condition for studying radiation effects is not straightforward to be determined when there is an interplay between electrical stress and ionizing radiation effects.